Exploration of Quantitative Ethnoveterinary Knowledge by Tribe in Harishchandra Gad Part of Northern Western Ghats (M.S), India - Kulbhushan W. Pawar,; Sanket P. Gawali,; S.A. Patil, (The Bioscan, 2025)
Out of 20 plant species, 13 families, and 17 species are the subjects of the current study's traditional ethno-veterinary knowledge. The residents' knowledge of living in the research region was examined. It contains bark, wood, root, tuber, and leaf from one tree, as well as seeds from three trees, leaves from six trees, trunks from two trees, fruit from four trees, and bark from two trees. Interviews were conducted verbally with informants from the research region informally at work. The informants were aged 16 to 90 years. Male informants (61.90%) and female informants (38.09%) reported having ethno-veterinary knowledge among the 42 participants. Numerous variables, including usage value, use report, and fidelity level, were examined through statistical data analysis. The medicinal properties of natural plants used in traditional domestic animal treatment systems have been validated by science, recognizing and valuing the traditional knowledge of local communities.